The Relationship between Pain Catastrophizing and Cognitive Function in Chronic Musculoskeletal Pain: A Scoping Review - Cory Alcon; Elizabeth Bergman; John Humphrey; Rupal M. Patel; Sharon Wang-Price (Pain Research and Management)
Objective. Chronic musculoskeletal pain (CMP) poses a considerable threat to physical, mental, and financial health worldwide. Beyond physical difficulties, CMP has a pronounced impact on pain behaviors and cognitive function. The purpose of this scoping review was to examine the relationship between pain catastrophizing (PC) and cognitive function in CMP, identify gaps in the literature, and provide future directions for research on the topic. Methods. Search strings were entered in the following databases: PubMed, CINAHL, Nursing and Allied Health, Ovid Emcare, PsycInfo, and Scopus. Data from the included articles were extracted thematically based on diagnostic classification and included author(s), year of publication, country, aim, sample, methods, intervention (if applicable), and key findings. Results. 30 articles were included after screening. The studied populations included patients with fibromyalgia, chronic low back pain, and CMP. Two studies were designed to assess the relationship between PC and cognition as the primary aim. The included studies demonstrated variable evidence regarding the relationship between PC and cognition. Only four studies included clinically relevant PC populations (i.e., Pain Catastrophizing Scale score >30), and all found significant correlations. Conclusion. Although evidence exists for the relationship between cognitive function and PC, there is a lack of rigorous research to indicate the strength of this relationship and the specific cognitive functions affected. The literature lacks appropriate populations needed to investigate clinically relevant PC and is limited by heterogeneous neuropsychological test batteries. Future research should include populations demonstrating the behaviors being studied, intentional analysis of outcomes, and appropriate cognitive tests.